A dedicated H‐beta meridian scanning photometer for proton aurora measurement. Issue 1 (20th January 2017) - Unick, Craig W.; Donovan, Eric; Connors, Martin; Jackel, Brian
Abstract: An instrument designed to measure the location and brightness of auroral emissions from energetic proton precipitation is described. This photometer scans from the north to south horizon with a stepper motor and mirror. The scans are configured in software for a 30 s cadence with equally spaced samples along a meridian at constant altitude. Broadband light is separated into two channels with a novel optical splitter. This splitter uses a filter that has high transmission for the signal channel and high reflection on both the long‐ and short‐wavelength sides to reflect the combined background passbands, directing each channel to its respective detector. The half‐cone angle and angle of incidence of this splitter filter allow for an overall compact optical design that also provides superior sensitivity in both signal and background channels. The signal channel is 3 nm wide full width at half maximum (FWHM) at 486.1 nm, and the background channel comprises two 3 nm wide FWHM passbands at 480 nm and 495 nm created by a single filter. Both of these channels are measured with photomultiplier tubes in photon‐counting mode. Calibrations indicate a response of around 1000 c/s per rayleigh. Data are currently acquired in 5 ms bins with a Nyquist frequency of 100 Hz. The first system (Forty‐Eight Sixty‐One (FESO)‐1) has been operating at Athabasca University since February 2014, and the second system (FESO‐2) was deployed at Lucky Lake, Saskatchewan, in October 2015. The improved sensitivity over legacy instruments and the simultaneous measurement of signal and background enable operation during intervals with dynamic electron aurora and scattered moonlight. Key Points: A novel H‐beta meridian scanning photometer has been designed and built New levels of sensitivity are available for H‐beta auroral photometry Novel filtering architectures for auroral photometry are described